Phase II study of retifanlimab in patients with recurrent locally advanced or metastatic Merkel cell carcinoma (POD1UM-201) - Federica Morano; Celeste Lebbe; Mark Cornfeld; Shailender Bhatia; Melissa Burgess; Giovanni Grignani; Piotr Rutkowski; Francesca Spada; Michele Guida; Chuan Tian; Caroline Gaudy-Marqueste; Roberta Depenni; et al. (Journal for ImmunoTherapy of Cancer)
Background POD1UM-201, an open-label, single-arm, phase II multiregional study, evaluated efficacy and tolerability of retifanlimab, a humanized monoclonal antibody targeting programmed cell death protein-1 (PD-1) in chemotherapy-naive patients with recurrent locally advanced or metastatic Merkel cell carcinoma (MCC).Methods Patients were enrolled across 34 sites in the USA, Canada, and Europe. Eligible patients were ≥18 years with confirmed recurrent advanced locoregional or metastatic MCC not amenable to surgery or radiation therapy, had not received previous systemic treatment, had measurable disease, and Eastern Cooperative Oncology Group performance status 0–1. Retifanlimab 500 mg was administered intravenously every 4 weeks (Q4W) for up to 2 years. The primary endpoint was objective response rate (ORR). Key secondary endpoints included duration of response (DOR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and safety.Results A total of 101 patients were enrolled between February 12, 2019, and June 16, 2021, with a median duration of follow-up for response of 22.2 (range: 1.1–55.3) months. ORR was 54.5% (95% CI: 44.2% to 64.4%; n=55), including 18 patients (17.8%) with complete responses (CRs) and 37 (36.6%) with partial responses (PRs). DCR was 60.4% (95% CI: 50.2% to 70.0%; n=61). Median DOR was not reached (95% CI: 14.0 months to not estimable (NE)) in patients who achieved CR and was 25.3 months (95% CI: 14.2 months to NE) in those with PR. With a median follow-up of 9.3 (range: 0.0–57.1) months, the estimated median PFS was 16.0 months (95% CI: 9.0 months to 32.2). Median OS was not reached with 63% of patients alive at 3 years. The safety profile was representative of the PD-(ligand)1 inhibitor class, with grade 3 immune-related adverse events occurring in 11 patients (10.9%).Conclusions Retifanlimab 500 mg Q4W led to frequent and durable responses in chemotherapy-naive patients with advanced MCC with an acceptable safety profile. Retifanlimab represents a new immunotherapy option for patients with locally advanced or metastatic MCC.Trial registration number NCT03599713; EudraCT 2018-001627-39